2015
DOI: 10.2174/0929867322666150821101047
|View full text |Cite
|
Sign up to set email alerts
|

Sesterterpenoids with Anticancer Activity

Abstract: Terpenes have received a great deal of attention in the scientific literature due to complex, synthetically challenging structures and diverse biological activities associated with this class of natural products. Based on the number of C5 isoprene units they are generated from, terpenes are classified as hemi- (C5), mono- (C10), sesqui- (C15), di- (C20), sester- (C25), tri (C30), and tetraterpenes (C40). Among these, sesterterpenes and their derivatives known as sesterterpenoids, are ubiquitous secondary metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 89 publications
1
35
0
Order By: Relevance
“…OphA is a phytotoxin produced by the fungal pathogen Drechslera gigantea and other Bipolaris spp (11,12). The sesterterpene-type compound (C25) is one of a group of over 25 Ophiobolin analogues (13), which are characterized by the unique 5-8-5 carbotricyclic skeleton (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…OphA is a phytotoxin produced by the fungal pathogen Drechslera gigantea and other Bipolaris spp (11,12). The sesterterpene-type compound (C25) is one of a group of over 25 Ophiobolin analogues (13), which are characterized by the unique 5-8-5 carbotricyclic skeleton (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are structurally diverse and have a wide spectrum of biological activities, ranging from antiinflammatory, anticancer, cytotoxic, and antimicrobial bioactivities to phytotoxicity and plant defense (1). Recent work on sesterterpenoids has suggested that this terpene class could be an important new source of anticancer drugs (2,3). The majority of sesterterpenoids characterized to date are from marine sponges and terrestrial fungi, with only ∼60-70 being of plant origin.…”
mentioning
confidence: 99%
“…C 25 GFPP is a precursor of sesterterpenoids, which are compounds with multiple bioactive properties and thus promising pharmacological potential [55]. They were occasionally reported in plants, but their origin had not been addressed until recently.…”
Section: Trans-prenyltransferasesmentioning
confidence: 99%